Congenital hemangioma in spondylocostal dysostosis: a novel association - Victor Michael Salinas-Torres (Sociedade Brasileira de Dermatologia, 2016)
Abstract Congenital hemangioma is a benign tumor caused by dysfunction in embryogenesis and vasculogenesis, which progresses during fetal life to manifest as fully developed at birth. Although hemangiomas are the most common tumor of infancy, rapidly involuting congenital hemangioma has not been described in spondylocostal dysostosis. I report the novel association of congenital hemangioma and spondylocostal dysostosis in a Mexican newborn female patient with neural tube defects. Given the embryological relationship between skin and nervous system, I surmise that this association is not coincidental. I also propose that these morphologic alterations be incorporated to the spondylocostal dysostosis phenotype and specifically looked for in other affected children, in order to provide appropriate medical management and genetic counseling.